Community-based environmental strategies to prevent the non-medical use of marijuana: A review of the literature. (4th July 2015) - Quinlan, Kristen J.; Valenti, Maria; Barovier, Linda; Rots, Gisela; Harding, Wayne
Abstract : Aims : To summarize published evidence for environmental strategies to prevent the non-medical use of marijuana (NMUM). Methods : Four databases (PSYCHINFO, SocINDEX, PsycARTICLES and Academic Search Complete) were searched for articles examining environmental strategies for NMUM prevention. Articles included were peer-reviewed, published in English between 2003 and 2013 and had full-text availability. The references listed in retrieved articles were included when they met selection criteria. Findings : Twenty articles met inclusion criteria. Seven described evaluations of media strategies to prevent marijuana use; eight examined the impact of policy on marijuana use (six described the impact of medical marijuana laws on use; two explored the impact of national-level policy and enforcement on use); and five explored price and availability and their impact on marijuana demand and use. Conclusions : Media prevention campaigns for NMUM work best when they are well-targeted and bolstered by community-level support. Marijuana-related policy studies on medical marijuana laws (MML) show inconsistent findings about their impact on NMUM. Unique distribution characteristics of marijuana make its use relatively insensitive to price fluctuations compared to other illicit drugs. Future research should focus on evaluation of: (a) policies that expand beyond MMLs, (b) marijuana enforcement strategies and (c) other types of state or local-level environmental strategies.